2020
DOI: 10.1049/iet-nbt.2020.0002
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles loaded with aspirin and 5‐fluororacil enable synergistic antitumour activity through the modulation of NF‐κB/COX‐2 signalling pathway

Abstract: Based on the enhancement of synergistic antitumour activity to treat cancer and the correlation between inflammation and carcinogenesis, the authors designed chitosan nanoparticles for co-delivery of 5-fluororacil (5-Fu: an as anti-cancer drug) and aspirin (a non-steroidal anti-inflammatory drug) and induced synergistic antitumour activity through the modulation of the nuclear factor kappa B (NF-κB)/cyclooxygenase-2 (COX-2) signalling pathways. The results showed that aspirin at non-cytotoxic concentrations sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…On the other hand, the beneficial effects of ASA on inflammation can also be explained by the decreased expression of COX-1, COX-2, TNFα, and IL-6 and the increased expression of anti-inflammatory IL-10. The inhibitory effect of ASA on COX-2 expression has also been shown in other recent studies, but the decrease in COX-2 expression could be promoted by the reduced levels of TNF-α as well [ 20 , 21 , 22 , 23 , 24 ]. In line with the results of our study, it has been shown that, in mice fed with a methionine- and choline-deficient diet, hepatic expression of COX-2 messenger RNA and protein was significantly higher than controls, paralleling the increase in the levels of TNF-α and IL-6 and the development of steatohepatitis; pharmacological inhibition of COX-2 ameliorated the severity of experimental steatohepatitis [ 25 ].…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, the beneficial effects of ASA on inflammation can also be explained by the decreased expression of COX-1, COX-2, TNFα, and IL-6 and the increased expression of anti-inflammatory IL-10. The inhibitory effect of ASA on COX-2 expression has also been shown in other recent studies, but the decrease in COX-2 expression could be promoted by the reduced levels of TNF-α as well [ 20 , 21 , 22 , 23 , 24 ]. In line with the results of our study, it has been shown that, in mice fed with a methionine- and choline-deficient diet, hepatic expression of COX-2 messenger RNA and protein was significantly higher than controls, paralleling the increase in the levels of TNF-α and IL-6 and the development of steatohepatitis; pharmacological inhibition of COX-2 ameliorated the severity of experimental steatohepatitis [ 25 ].…”
Section: Discussionsupporting
confidence: 62%
“…Transcription of COX-2 is thought to be promoted by NF-κB. Aspirin modifies both NF-κB signaling and COX-2 expression ( 116 ), and has been shown to have therapeutic effects in several tumors with high COX-2 levels ( 117 , 118 ). Although some studies have shown that aspirin may halt VS growth ( 119 , 120 ), the latest meta-analysis disproved this viewpoint ( 121 ).…”
Section: Resultsmentioning
confidence: 99%
“…have therapeutic effects in several tumors with high COX-2 levels (117,118). Although some studies have shown that aspirin may halt VS growth (119,120), the latest meta-analysis disproved this viewpoint (121).…”
Section: Cyclooxygenase-2 (Cox-2)mentioning
confidence: 99%
“…Additionally, some literature reports include combined targeting of different reactive agents to obtain synergistic antitumor activity. Based on this assumption, nonsteroidal anti-inflammatory aspirin was co-loaded with 5-FU in chitosan NPs [ 63 ]. Aspirin contributed to reduced cell viability and thus strengthened the antitumor effect of 5-FU.…”
Section: Cs Np Platforms For a Specific Drug Deliverymentioning
confidence: 99%